Management Strategy of BCCT Model Implementation in Improving the Quality of Early Childhood Learning: Case Study in Tasikmalaya - Hasani, Syarief (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
Beyond Center and Circle Time (BCCT) is a student-centered learning approach, namely learning activities are centered on the play center and activities in a circle. In BCCT, children are invited to assimilate new information into previous knowledge and experience. They are also invited to accommodate new knowledge by expanding or changing existing knowledge schemes. This study aims to analyze the management of the use of the Beyond Center and Circle Time (BCCT) learning model in improving the quality of early childhood learning at RA Baiturrahman, Tasikmalaya City. The case study method was chosen as the method in this study because the problems studied occurred in certain places and situations. Based on the results of the study from the data obtained in the field and the discussion, it can be concluded that the Beyond Center and Circle Time (BCCT) learning model can improve the quality of early childhood learning at RA Baiturrahman, Tasikmalaya City. The evaluation results obtained are used as material for improvement in efforts to improve the quality of learning. There are several problems faced in implementing the BCCT learning model related to the capacity of teachers, students, facilities and infrastructure, and financing.